Successful Surgical Management of a Thrombosed Temporary Inferior Vena Cava Filter - Sueshiro, Masahumi; Ishii, Osamu; Tamura, Kentaro (Japanese Journal of Vascular Surgery, 2009)
Background: Although the inferior vena cava filter is effective for protection against pulmonary embolism associated with deep vein thrombosis, several kinds of complications have been reported. Patient and method: A 79-year-old woman who suffered from dyspnea was admitted with deep vein thrombosis and pulmonary thromboembolism. Protein S deficiency was revealed by a significant decrease in protein S activity. A temporary inferior vena cava filter (tIVCF) was inserted to prevent new pulmonary thromboembolism. After 13 days of anti-coagulant therapy, cavography revealed complete occlusion of the vena cava at the tIVCF. We tried catheter-directed thrombolysis and catheter thrombectomy, but were unsuccessful. The patient then underwent vena cava ligation under open laparotomy. The surgery was successful and she was discharged on post-operative day 20. Conclusion: Although this is a rare complication, we must carefully observe patients after insertion of temporary inferior vena cava filters.